Efek Takaran Biochar dan Jenis Kacang terhadap Pertumbuhan dan Hasil Kacang dalam Sistem Tumpangsari Salome pada Lahan Kering - Maria Yunovi Biamnasi (Savana Cendana, 2021)
Planting corn and some types of beans are two types of plants suitable to be applied in the salome intercropping system on dry land. This study aims to determine the effect of biochar on the growth and yield of several types of beans which are grounded with corn on dry land. To find out the interaction of biochar on the growth and yield of several types of peanuts intercropped with salome with corn on dry land. This research was conducted by experimental gardens of the Faculty of Agriculture, Unimor, in June until November 2018. Using a Randomized Block Design. Factorial repeated three times. The first factor is the use of biochar which consists of two levels, namely without biochar and use of biochar. The second faktor is the type of upright local beans, namely green beans, rice beans and red beans. There was no interaction between the biochar treatment and the type of beans intercropped with maize on all observed parameters. Addition of biochar into the soil caused several parameters of growth and crop yield to be lower than controls such as plant height, leaf number, weight of 100 seeds, seed weight per plot, and harvest index. The type of beans that are intercropped with corn with the salome method is best produced by Phaseolus vulgaris beans.